Implementasi EDM dalam Penjaminan Mutu Pendidikan DI MI Tahfidzul Qur'an AL Manar - Maulana, Era Carica; Rohmadi, Yusup; Permatasari , Selina Indah (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the implementation of Madrasah Self-Evaluation at MI Tahfidzul Qur'an Al Manar Klaten in Education Quality Assurance. The decline in the quality of education in Indonesia reinforces the need for seriousness in implementing EDM at every level, especially in basic education. The approach used in this study is a qualitative-descriptive approach. Researchers deepen the various phenomena that exist in the field and describe them in the form of words and sentences. The methods used by researchers in collecting data are direct observation, in-depth interviews, and documentation analysis. Researchers used Miles and Huberman's model in conducting data analysis, namely data collection, data reduction, data display, and data conclusions/verification. In the instrument development stage using instruments from the Government with reference to the eight SNPs. At the data collection stage using instruments filled out by the head of the madrasa, eight teachers, fifteen students, three madrasah committees by providing assistance and verifying data entry. At the data analysis stage using the EDM application and determine the problem. All stakeholders analyze the root/cause of the problem. At the recommendation stage, stakeholders determine the priority of problems from the most urgent things for improvement. The results showed a significant effect. The constraints experienced were a lack of funds and a lack of role from the government in terms of financial assistance